Gothic Animals
XIX, 310 p. 6 illus., 2 illus. in color.
Keywords: This book begins with the assumption that the presence of non-human creatures causes an always-already uncanny rift in human assumptions about reality. Exploring the dark side of animal nature and the ‘otherness’ of animals as viewed by humans, and employing cutting-edge theory on non-human animals, eco-criticism, literary and cultural theory, this book takes the Gothic genre into new territory. After the dissemination of Darwin’s theories of evolution, nineteenth-century fiction quickly picked up on the idea of the ‘animal within’. Here, the fear explored was of an unruly, defiant, degenerate and entirely amoral animality lying (mostly) dormant within all of us. However, non-humans and humans have other sorts of encounters, too, and even before Darwin, humans have often had an uneasy relationship with animals, which, as Donna Haraway puts it, have a way of ‘looking back’ at us. In this book, the focus is not on the ‘animal within’ but rather on the animal ‘with-out’: otherand entirely incomprehensible. Ruth Heholt is a senior lecturer in English at Falmouth University. She has published widely on the topics of the Gothic, crime, gender and the supernatural. She is currently completing a monograph on the Victorian writer Catherine Crowe and is editor of the journal Revenant: Critical and Creative Studies of the Supernatural. Melissa Edmundson is a lecturer in English at Clemson University and specializes in nineteenth- and twentieth-century women writers and supernatural fiction. She is the author of Women’s Ghost Literature in Nineteenth-Century Britain (University of Wales Press, 2013) and Women’s Colonial Gothic Writing, 1850-1930: Haunted Empire (Palgrave Macmillan, 2018).